1999
DOI: 10.1103/physrevb.60.15550
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic theory of an electron gas

Abstract: The generalised hydrodynamic theory of an electron gas, which does not rely on an assumption of a local equilibrium, is derived as the long-wave limit of a kinetic equation. Apart from the common hydrodynamics variables the theory includes the tensor fields of the higher moments of the distribution function. In contrast to the Bloch hydrodynamics, the theory leads to the correct plasmon dispersion and in the low frequency limit recovers the Navies-Stocks hydrodynamics. The linear approximation to the generalis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
123
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 21 publications
5
123
0
Order By: Relevance
“…These are the questions we address in the present paper. In the short publication 13 we showed that such hydrodynamics existed. In the paper Ref.…”
Section: Introductionmentioning
confidence: 95%
“…These are the questions we address in the present paper. In the short publication 13 we showed that such hydrodynamics existed. In the paper Ref.…”
Section: Introductionmentioning
confidence: 95%
“…Higher moments of the Vlasov equation, which could yield a hydrodynamic closure like in Refs. [37][38][39][40], can be obtained analogously, and most easily for a nonrelativistic motion (γ ≈ 1). Those are not discussed here, but are addressed separately in our Ref.…”
Section: Hydrodynamic Equationsmentioning
confidence: 99%
“…In this paper we will adapt the latter name. Of course, there are many further refinements of the HT that go beyond the QHT [18,19,[61][62][63][64][65][66]. Obviously, the more advanced theory usually involves a more complicated P, which makes the numerical investigation even more expensive.…”
Section: Introductionmentioning
confidence: 99%